Salmonella enteritidis ventriculitis - Jamaluddin, Johan Aref; Hung, Liang Choo; Othman, Norlijah (SEAMEO Regional Tropical Medicine and Public Health Network, 2013)
Salmonella sp are important causes of meningitis among neonates and young children in Malaysia. We present a case of Salmonella enteritidis meningitis in a six week old female who presented with a one week history of fever, diarrhea and seizures which was unsuccessfully treated with a third generation cephalosporin. She had a relapse of meningitis complicated with ventriculitis and hydrocephalus, requiring an eleven week course of meropenem. She improved clinically, but did not have improvement in the cerebrospinal fluid (CSF) glucose level despite prolonged antibiotic use. This case illustrates the dilemma in determining the duration of antibiotic needed to successfully treat Salmonella enteritidis ventriculitis.